Isolasi dan Identifikasi Bakteri Pendegradasi Fenol yang Bersumber Dari Danau Tempe Kabupaten Wajo Sulawesi Selatan - Fitriana Fitriana; Maswati Baharuddin; Sappewali Sappewali (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2016)
Water pollution in Tempe Lake was consequence by people activity in around of Tempe Lake, such as domestic waste and agriculture waste. One of the dangerous pollutions which was resulted from the waste was phenol pollution. Phenol waste reduction efforts on Tempe Lake could be solved by biodegradation process using bacteria. This research aimed to: 1) Get the bacteria which was able to degrade phenol on samples sourced from Tempe Lake, Wajo South Sulawesi and 2) Identify the type of bacteria that can degrade phenol sourced from Lake Tempe, Wajo South Sulawesi. The Metods used in the research was making of media, isolation and purification of bacteria, identification of bacteria and testing the ability of phenol degradation. Bacterial identification tests include staining gram and biochemical tests (TSIA, SIM, MR-VP, urea, citric and sugar fermentation). The degradation test was performed using UV-Vis spectrophotometry with colorimetric method using follin reagent. The results showed that the bacterial identified as the genus Enterobacter spp and Klebsella spp which were gram negative bacteria. Test of phenol degradation at 48 hour incubation using UV-Vis shows that bacterial isolates C1F was able to degrade phenol 500 ppm to 3,091 ppm, bacterial isolate S1F was able to degrade phenol 500 ppm to 5,1153 ppm and bacterial isolate H2F was able to degrade phenol 500 ppm to 7,7834 ppm.